Guinea-Bissau : Review of Performance Under the Program Supported by Emergency Post-Conflict Assistance and Request for Second Purchase Under Emergency Post-Conflict Assistance-Staff Report; Press Release on the Executive Board Discussion; and Statement by the Executive Director for Guinea-Bissau. (IMF Staff Country Reports; Country Report, 2008)
This paper reviews the performance of Guinea-Bissau Under the program supported by Emergency Post-Conflict Assistance (EPCA). Guinea-Bissau has made progress in stabilizing its fiscal situation under difficult circumstances and is moving steadily to implement structural reforms. Four of the six end-March quantitative indicators were met; the other two are expected to be met for the year as a whole. All structural indicators were implemented, albeit with some delay. The authorities recognize the importance of accelerating structural fiscal reforms to further build capacity and improve confidence in the economy.